ANALISIS PENERIMAAN PAJAK DI DIY DAN FAKTOR YANG MEMPENGARUHINYA - DESY EFITRIANA; RIFKI KHOIRUDIN (LP2MTBM MAKARIOZ, 2021)
The purpose of this study was to analyze the factors that influence the advertisement tax revenue of Province D.I.Yogyakarta2012-2019.the data used is panel data, which is a combination of cross-section data and time series in the province ofD.I.Yogyakarta for the period 2012-2019, using the panel data regression method with eviews 9.the test resultssimultaneously show that the overall independent variables (Economic Growth, Total Population, number of Industry,numberof Tourists Outside D.I.Yogyakarta and Road Length) together can show a significant effect on billboard tax revenue inProvince Yogyakarta and partial testing shows that the number of residents and the number of tourists outsideD.I.Yogyakarta have not effect on advertisement tax revenue.